Impact of maternal Bisphenol A exposure on thyroid hormones and birth anthropometric outcomes: A repeated measures study - Iman Al-Saleh; Rola Elkhatib; Maha Alnemer; Hesham Aldhalaan; Mohamed Shoukri (Emerging Contaminants)
We investigated the effects of prenatal bisphenol A (BPA) exposure on maternal thyroid hormones and fetal growth outcomes within a cohort from Saudi Arabia. In this prospective study, 672 pregnant women provided 1957 urine samples, which were analyzed for BPA concentrations using UPLC-MS/MS throughout three trimesters. We recorded BPA detection rates and median concentrations, using mixed-effects models to examine the influence on maternal thyroid hormones, specifically free thyroxine (FT4) and thyroid-stimulating hormone (TSH). Additionally, we explored the impact on fetal growth markers such as head circumference (HC) and placental weight (PWT) through multivariable regression, adjusting for confounders. Findings indicated that BPA was present in over 95 % of samples, with a notable decrease in median concentrations from the 1st to the 3rd trimester. Higher BPA exposure correlated with a 2.96 % increase in FT4 levels and a 14.58 % reduction in TSH in the top exposure quartile. Fetal growth analysis showed a decrease of 3.8 % in HC and 15.3 % in PWT associated with high first-trimester BPA levels. Furthermore, FT4 levels in the first and 2nd trimesters mediated the relationship between BPA exposure and fetal growth outcomes by 21.1 % for PWT and 19.1 % for HC, while gestational age mediated 12.1 % of the change in HC. The study highlights significant disruptions in thyroid function and detrimental effects on fetal development due to high BPA exposure, underscoring the need for rigorous monitoring and preventive measures during pregnancy.